CM247LC 초내열합금에서 일방향응고 스타트 블록의 초기 핵생성 조건에 따른 결정립 성장 - 윤혜영; Hye Young Yoon; 이재현; Je Hyun Lee; 정형민; Hyeong Min Jung; 서성문; Seong Moon Seo; 조창용; Chang Young Jo; 권석환; Seok Hwan Gwon; et al. (대한금속·재료학회지, 49(1), 2011)
The grain size and growth direction of a directionally solidified turbine blade were evaluated by the initial nucleation condition at the start block of directional solidification. The initial nucleation condition was controlled by inserting a Ni foil on the directional solidification plate of the directional solidification furnace. Fine grains with good orientation were obtained in the faster cooling condition at the start block. The nucleus number was compared with the cooling rate of the start block by electron back scattered diffraction (EBSD). DSC (differential scanning calorimeter) analysis was performed to compare the melting point and undercooling for nucleation of the coarse nuclei and fine nuclei of the start block. The faster cooling condition at the start block showed more undercooling for nucleation and smaller size of nuclei which resulted in a fine grain with good orientation in the directional turbine blade.